2009
DOI: 10.1111/j.1469-0691.2008.02122.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between galactomannan antigen levels in serum and neutrophil counts in haematological patients with invasive aspergillosis

Abstract: The detection of circulating galactomannan (GM) in serum samples is an important step in the diagnosis of invasive aspergillosis (IA). The assay has been mainly explored in neutropenic patients, and is now used to monitor patients at high risk for IA. However, the performance of the assay varies greatly among studies. The objective of this study was to explore the impact of the neutrophil count on the GM serum index at the time of IA diagnosis. Ninety-nine episodes of proven or probable, microbiologically docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 28 publications
1
63
0
9
Order By: Relevance
“…Nötropenik olmayan İPA olgularında infl amatuar yanıtın fazla olması nedeniyle, fungal yükün ve damar invazyonunun daha az olması, bu olgularda serum GM duyarlılığındaki azalmanın en önemli nedenidir. Ayrıca immün sistemi normal hastalarda, GM antijeninin dolaşımdan temizlendiği ve nötrofi l sayısının artması ile serum GM antijenin tanı değerinin düştüğü de, yapılan çalışmalarla gösterilmiştir 22 .…”
Section: İstatistiksel Analizunclassified
“…Nötropenik olmayan İPA olgularında infl amatuar yanıtın fazla olması nedeniyle, fungal yükün ve damar invazyonunun daha az olması, bu olgularda serum GM duyarlılığındaki azalmanın en önemli nedenidir. Ayrıca immün sistemi normal hastalarda, GM antijeninin dolaşımdan temizlendiği ve nötrofi l sayısının artması ile serum GM antijenin tanı değerinin düştüğü de, yapılan çalışmalarla gösterilmiştir 22 .…”
Section: İstatistiksel Analizunclassified
“…5 Differences in performance of the EIA are probably due to differences in the pathogenesis of Aspergillus diseases in various host groups. [6][7][8][9] In neutropenic patients, angioinvasive aspergillosis occurs, which is associated with an invasion of blood vessels due to a poor immune response. In non-neutropenic patients, such as hematological patients after BM recovery or non-hematological patients treated with long-term corticosteroids and other immunosuppressive regimens, a significant local inflammation limiting the angio-invasive process occurs.…”
Section: Galactomannan (Gm)mentioning
confidence: 99%
“…Although the performance of serum GM testing seems to be promising only in neutropenic patients, who usually develop angioinvasive forms of IPA (1,16), bronchoalveolar lavage (BAL) fluid (BALF) GM seems the method of choice in nonneutropenic patients who tend to develop airway-invasive forms (17)(18)(19). This was confirmed in a study evaluating patients with underlying structural damage of the lung tissue (e.g., COPD, emphysema, bronchiectasis), which found that only one out of 65 patients with COPD with IPA had a positive serum GM test (8).…”
mentioning
confidence: 99%